Application of Gastric Tube Decompression for Rapid Tip Positioning in Bedside Blind Insertion of Nasoenteric Tubes - Yang LL; Li DN; Gao P; Zhang H; Wang J (Journal of Multidisciplinary Healthcare)
Li-Li Yang,1 Di-Na Li,1 Peng Gao,2 Hua Zhang,1 Juan Wang3 1Department of Emergency, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China; 2Department of Medical Affairs, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China; 3Department of Hepatobiliary Pancreatic Surgery, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of ChinaCorrespondence: Di-Na Li, Department of Emergency, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China, Tel +86 18236933790, Email lidnina_lii@126.comObjective: This study aims to examine the efficacy of gastric tube decompression in rapid tip positioning during bedside blind insertion of nasoenteric tubes.Methods: Between August 2023 and July 2024, patients who were critically ill in the emergency intensive care unit of a tertiary hospital in Beijing who required nasoenteric tube placement were enrolled in this study. Gastric tube decompression was used to facilitate the tip positioning of nasoenteric tubes inserted blindly (without direct visualization), at the bedside. The accuracy of this method was verified by comparing the results to the “gold standard” of abdominal X-ray imaging. Consistent results indicated successful positioning. Additionally, the number of positioning attempts, time taken, and associated adverse events were recorded as outcome indicators.Results: A total of 55 patients who were critically ill were included in the study, achieving a positioning conformity rate of 98.18% (54/55). The first-time positioning conformity rate was 94.55% (52/55). The median time for positioning attempts was 21 minutes (18, 28 minutes). The sensitivity was recorded at 100%, and no related adverse events were reported.Conclusion: Gastric tube decompression can rapidly and accurately determine the position of the nasoenteric tube tip, providing a safe and convenient method with a high accuracy rate. This technique enhances the safety of long-term nasoenteric tube placement in patients who are critically ill and enhances the efficiency of blind nasoenteric tube insertion.Keywords: bedside blind insertion, critically ill patients, gastric tube decompression, nasoenteric tube, positioning